Development of Safe and Scalable Continuous-Flow Methods for Palladium-Catalyzed Aerobic Oxidation Reactions - Ye, Xuan (2010)
The synthetic scope and utility of Pd-catalyzed aerobic oxidation reactions has advanced significantly over the past decade, and these reactions have potential to address important green-chemistry challenges in the pharmaceutical industry. This potential has been unrealized, however, because safety concerns and process constraints hinder large-scale applications of this chemistry. These limitations are addressed by the development of a continuous-flow tube reactor, which has been demonstrated on several scales in the aerobic oxidation of alcohols. Use of a dilute oxygen gas source (8% O(2) in N(2)) ensures that the oxygen/organic mixture never enters the explosive regime, and efficient gas-liquid mixing in the reactor minimizes decomposition of the homogeneous catalyst into inactive Pd metal. These results provide the basis for large-scale implementation of palladium-catalyzed (and other) aerobic oxidation reactions for pharmaceutical synthesis.